Impact of the first phase of movement control order during the COVID-19 pandemic in Malaysia on purchasing behavior of Malaysian consumers - Kamaljeet, K.; Mageswari, K.; Jaspal, S. J. S. *; Selvi, S.; Sukjeet, K. S. (BP Services, 2020)
With the COVID-19 pandemic, countries around the world are affected and taking drastic steps to curb the spread of the virus by implementing Movement Control Order (MCO) and lockdowns. The feeling of depression and uncertainty of many Malaysians have resulted into a sense of panic and fear. The aim of this study is to explore Malaysian consumers’ consumption behavior during the first phase of MCO due to COVID-19. This study employed Theory Planned Behavior as an underpinning theory to explain consumer behavior during this pandemic. 231 respondents were chosen using convenience sampling technique. The data was analyzed and interpreted using the statistical package SPSS and version 3.2.9 of the Structural Equation Modeling Partial Least Square (SEM-PLS). The study showed mass and social medias inputs were influential in assessing the severity of the crisis, and thereby impacting the shopping experience. This study confirmed that Malaysian Fear of Missing Out (FoMO) was a vital variable in purchasing behavior during the MCO’s first phase.